1984
DOI: 10.1002/jlac.198419840115
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselektive Synthese von (1RS)‐endo‐Brevicomin

Abstract: (1RS)-endo-Brevicomin (1) wird ausgehend von fruns-1-Brom-2-penten synthetisiert. Schliisselreaktion ist die diastereoselektive Verknupfung von erythro-2,3-ButandioI mit 3,3-Dimethoxy-1-(phenylsu1fonyl)butan oder 4,4-Dimethoxypentanslure-methylester. Diastereoselective Synthesis of (YZS)-endo-Brevicomin(1RS)-endo-Brevicomin (1) is synthesized starting from rruns-1 -bromo-2-pentene. Synthetic key step is the diastereoselective linkage of erythro-2,3-butanediol to 3,3-dimethoxy-l-(phenylsulfonyl)-butane or methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In 1982, Masaki et al reported the total synthesis of (+)- exo -brevicomin ( 15a ) via dioxolane formation ( 29 + 30 → 31 ) and intramolecular S N 2 substitution ( 32 → 33 ) as the key steps for the 6,8-DOBCO framework (Scheme a). Subsequently, Scharf et al employed the similar strategy for total syntheses of several 6,8-DOBCO pheromones. In 1995, Sharf achieved the first total synthesis of racemic β-multistriatin by a new tactic for the 6,8-DOBCO: an intramolecular cycloketalization for the dioxolane formation ( 34 → 35 ) and intramolecular aldol condensation ( 35 → 36 ), to avoid the facile epimerization of C-2 axial methyl group under mild acidic condition (Scheme b).…”
Section: General Strategies Toward 68-dobcosmentioning
confidence: 99%
“…In 1982, Masaki et al reported the total synthesis of (+)- exo -brevicomin ( 15a ) via dioxolane formation ( 29 + 30 → 31 ) and intramolecular S N 2 substitution ( 32 → 33 ) as the key steps for the 6,8-DOBCO framework (Scheme a). Subsequently, Scharf et al employed the similar strategy for total syntheses of several 6,8-DOBCO pheromones. In 1995, Sharf achieved the first total synthesis of racemic β-multistriatin by a new tactic for the 6,8-DOBCO: an intramolecular cycloketalization for the dioxolane formation ( 34 → 35 ) and intramolecular aldol condensation ( 35 → 36 ), to avoid the facile epimerization of C-2 axial methyl group under mild acidic condition (Scheme b).…”
Section: General Strategies Toward 68-dobcosmentioning
confidence: 99%